Synthesis Polymer Matrix Composite Epoxy-FeNdB-Mn for Radar Absorbing Material Application - Juniansyah, Gibran; Lathifah, Sri Mulyati; Prajitno, Djoko Hadi (International Journal of Mechanical Engineering Technologies and Applications, 2021)
In recent years, applications using electromagnetic wave technology have grown rapidly. One of them is in the military field, the wave-absorbing material used to avoid detection such as aircraft, ships, or tanks requires a super thin absorbent material which has extraordinary absorption. One of the criteria for a wave absorbing material is a soft magnet and has a high Reflection Loss (RL). This research aims to see the effect of the addition of FeNdB and Mn on the synthesis of Polymer Matrix Composite (PMC) as a wave-absorbing material.The FeNdB milling process and Mechanical Alloying (MA) with Mn were carried out using a Planetary Ball Mill (PBM) at a speed of 1000 rpm for 60 minutes. synthesis of PMC by varying the composition of epoxy resin with magnetic powder 95: 5; 90:10; 85: 5. Based on the characterization results, the optimum RL was obtained at a composition of 85: 5 with a value of -22.40 dB at a frequency of 10.40 GHz and the magnetic properties after the addition of Mn were obtained HcJ 0.116 kOe and Br 0.41 kG. PMC hardness increased with the increase of powder in the sample with the highest value of 29.2 HD Shore D and the adhesion decreased with the addition of powder in the sample with the lowest value of 1 MPa.